Comprehensive nutritional compositions of traditional dishes from five Saudi regions using Elizabeth Stewart Hands and Associates Food Processor software - Basaqr, Reem; Bakr, El-Sayed; Ibrahim, Yasmine; Bujan, Yassmin; Alqasimi, Kholoud; Aljaadi, Abeer (Frontiers in Nutrition, 2025)
IntroductionComprehensive nutritional information on the recipes of traditional Saudi dishes, an integral part of the country’s culinary heritage, is lacking. This study analyzed the nutritional composition of 25 commonly consumed traditional dishes from five Saudi Arabian regions using the Elizabeth Stewart Hands and Associates (ESHA) Food Processor Nutrition Analysis software.MethodsA cross-sectional study was conducted online using convenience sampling to identify commonly consumed traditional Saudi dishes. Overall, 360 individuals responded to the survey. Of these, follow-up phone interviews were conducted with 61 household recipe providers who had prepared the selected dishes at least five times in the past year and provided complete recipe data. Ingredients were weighed or converted to grams using food amount booklets. Nutrient values of the traditional dish recipes were estimated using the average of multiple recipes and software estimates per dish (a total of 75 recipes, three recipes for each cuisine), accounting for variations in ingredient amounts and preparation methods. The nutrient data are presented per 100 g and portion size.ResultsThe nutritional compositions of the selected dish recipes varied. The moisture, protein, fat, fiber, and carbohydrate contents were 5.7–80.4%, 3.4–13.0%, 2.0–13.3%, 0.26–5.8%, and 5.9–50.1%, respectively. The highest energy content per 100 g was found in Areekah (306.9 kcal) and the lowest was found in Margoug (89.2 kcal).ConclusionRecipe-based ESHA estimation provided valuable insights into the nutritional value of traditional Saudi dish recipes, serving as a resource for dietary planning, public health initiatives, and future research. The nutritional profiles generated in this study may contribute to the development of accurate and culturally-appropriate dietary recommendations and exchange lists for Saudi Arabia.